Contribution to the phylogeny of Caucasian Nonea (Boraginaceae) inferred from nrDNA ITS and trnL-F data - Güzel, Murat Erdem; Karimov, Vugar; Makbul, Serdar; Coşkunçelebi̇, Kami̇l (Phytotaxa, 2019)
Nonea (Boraginaceae) with nearly 35 species was divided into four sections based on the shape of mericarpids and the position of the anthers in the corolla tube. Although several comprehensive taxonomic studies have been performed on Turkish and European Nonea taxa, Caucasian ones have not been studied well. Therefore Caucasian Nonea need close attention with regard to molecular systematics. In this study, 15 Caucasian Nonea including N. cyanocalyx and N. bakuensis were evaluated with nrDNA ITS and cpDNA trnL-F sequence data using Maximum Parsimony and Bayesian Inference to reconstruct phylogeny. All examined members of Nonea were grouped at three main clades with weak to good support values based on nrITS and at two main clades with moderate to good support values based on trnL-F. Both trees did not coincide with the traditional sub-generic delimitation of Nonea, but nrITS tree supported monophyly of Nonea. On the other hand, Pulmonaria is deeply nested in Nonea in the trnL-F tree. Moreover, present findings support treating N. cyanocalyx and N. bakuensis as distinct species rather than subspecies and revealed a preliminary phylogenetic structure of little known Caucasian Nonea.